UHPLC-MS Characterization and Biological Insights of Different Solvent Extracts of Two Achillea Species (A. aleppica and A. santolinoides) from Turkey - Reneta Gevrenova; Gokhan Zengin; Kouadio Ibrahime Sinan; Evren Yıldıztugay; Dimitrina Zheleva-Dimitrova; Carene Picot-Allain; Mohamad Fawzi Mahomoodally; Muhammad Imran; Stefano Dall'Acqua (MDPI AG, 2021)
In the current study, Achillea santolinoides and Achillea aleppica aeral parts and root were extracted with ethyl acetate, methanol, and water. Detailed phytochemical profiles were obtained using UHPLC-MS, yielding the identification of hydroxybenzoic and hydroxycinnamic acids, phenolic acid glycosides and sugar esters, acylquinic acids, O-glycosyl flavones and flavonols, and flavonoid aglycons, among others. The antioxidant properties and enzyme inhibitory activities of the extracts were assayed with in vitro tests. The phenolic content of the water extracts was significantly higher as compared to the ethyl acetate and methanol ones. A. aleppica aerial parts methanol extract possessed highest flavonoid content (49.18 mg rutin equivalent/g). Antioxidant properties assessment revealed that the methanol extract of A. santolinoides roots actively scavenged DPPH (54.11 mg TE/g) and ABTS radicals (112.53 mg TE/g) and possessed highest reducing potential (183.55 and 129.92 mg TE/g, for CUPRAC and FRAP, respectively). The ethyl acetate extracts of aerial parts and roots of both species showed highest inhibition against BuCHE (6.07-6.76 mg GALAE/g). The ethyl acetate extract of A.santolinoides aerial part showed highest inhibition against tyrosinase (73.00 mg KAE/g). These results showed that the tested Achillea species might represent novel phytotherapeutic avenues for the management of Alzheimer's disease and epidermal hyperpigmentation conditions, which are both associated with oxidative stress. This paper could shed light into future potential industrial applications using the tested Achillea species.